Different oral and gut microbial profiles in those with Alzheimer's disease consuming anti-inflammatory diets - Chen, Lili; Wang, Bixia; Liu, Jinxiu; Wu, Xiaoqi; Xu, Xinhua; Cao, Huizhen; Ji, Xinli; Zhang, Ping; Li, Xiuli; Hou, Zhaoyi; Li, Hong (Frontiers in Nutrition, 2022)
The number of people living with Alzheimer’s disease (AD) is increasing alongside with aging of the population. Systemic chronic inflammation and microbial imbalance may play an important role in the pathogenesis of AD. Inflammatory diets regulate both the host microbiomes and inflammatory status. This study aimed to explore the impact of inflammatory diets on oral-gut microbes in patients with AD and the relationship between microbes and markers of systemic inflammation. The dietary inflammatory properties and the oral and gut microorganisms were analyzed using the dietary inflammatory index (DII) and 16S RNA in 60 patients with AD. The α-diversity was not related to the DII (p>0.05), whereas the -diversity was different in the oral microbiomes (R²=0.061, p=0.013). In the most anti-inflammatory diet group, Prevotella and Olsenella were more abundant in oral microbiomes and Alistipes, Ruminococcus, Odoribacter, and unclassified Firmicutes were in the gut microbiomes (p<0.05). Specific oral and gut genera were associated with interleukin-6 (IL)-6, complement 3 (C3), high-sensitivity C-reactive protein (hs-CRP), IL-1β, IL-4, IL-10, IL-12, and tumor necrosis factor-α (TNF-α) (p<0.05). In conclusion, anti-inflammatory diets seem to be associated with increased abundance of beneficial microbes, and specific oral and gut microbial composition was associated with inflammatory markers.